Single-Step Capsular Transformation and Acquisition of Penicillin Resistance in Streptococcus pneumoniae - Trzciński, Krzysztof (American Society for Microbiology, 2004)
The capsule (cps) locus of Streptococcus pneumoniae is flanked by the pbp2x and pbp1a genes, coding for penicillin-binding proteins, enzymes involved in cell wall synthesis that are targets for β-lactams. This linkage suggested to us that selection for β-lactam resistance might coselect for capsular transformants. The recombination event would then involve PBP genes, as well as the cps operon, and would change both the serotype and the resistance profile of the strain. We transformed β-lactam-susceptible strain TIGR4 by using whole genomic DNA extracted from multidrug-resistant strain GA71, a serotype 19F variant of pneumococcal clone Spain(23F)-1, and selected β-lactam-resistant transformants. Smooth colonies appearing on selective plates were subcultured, serotyped by the Quellung reaction, and genotyped to confirm the presence of the GA71 pbp2x-cps19-pbp1a locus in the TIGR4 genetic background by restriction fragment length polymorphism analysis of the whole locus and its flanking regions. The results showed that a new serotype, combined with resistance to β-lactams, could emerge in a susceptible strain via a single transformation event. Quantitative analysis showed that transfer of the cps locus had occurred at an elevated rate in β-lactam-selected transformants. This suggests that in natural settings selection by host immunity and selection by antibiotics may be interrelated because of “hitchhiking” effects due to linkage of resistance determinants and the capsule locus.